2008
DOI: 10.1007/s11664-008-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

Reflectivity and Abnormal Absorption at ITO/Al Interface

Abstract: The electrical and optical thermal stability of indium tin oxide (ITO)/Al bilayers are investigated in this study. The electrical resistivity of ITO and ITO/Al multilayers, both about 1 9 10 -3 X cm after annealing at 300°C for 1 min, are measured by the four-probe measurement method. In addition to the electrical measurements, we also observe the rapid initial diffusion of Al atoms into the ITO thin films. When the diffusing elemental Al atoms occupy interstitial sites they tend to form defects, causing a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Indium tin oxide (ITO) is widely used as transparent contact layers in traditional GaN-based blue and green LEDs. However, there is serious light absorption in the ITO in the ultraviolet band due to the band gap of ITO ranging from 3.5 eV to 4.3 eV [10,11]. Previous studies reported that doping metals in ITO would reduce the light absorption in near UV LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Indium tin oxide (ITO) is widely used as transparent contact layers in traditional GaN-based blue and green LEDs. However, there is serious light absorption in the ITO in the ultraviolet band due to the band gap of ITO ranging from 3.5 eV to 4.3 eV [10,11]. Previous studies reported that doping metals in ITO would reduce the light absorption in near UV LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the TCFs of bilayer structure, e.g., semiconductor/semiconductor [16][17][18] and semiconductor/metal [19][20][21] bilayer films, were studied by some authors. On the other hand, TCF/metal/TCF trilayer structures 22 were rapidly developed since they might provide optical and electrical characteristics superior to those single-layer or bilayer TCFs.…”
Section: Introductionmentioning
confidence: 99%